C, N and P dynamics during litter decomposition in pure and mixed beech – conifer stands: Effects of litter species, site conditions and native vs non-native conifer species - Stuckenberg, Thalea; Lu, Jing-Zhong; Scheu, Stefan (Forest ecology and management, 2025)
The plantation of mixed forests including non-native tree species is increasing but its impacts on litter decomposition and nutrient cycling remains little studied across different site conditions. Using litterbags with European beech leaves, Norway spruce or Douglas-fir needles, we investigated litter decomposition processes in monocultures and mixed forests of European beech, Norway spruce and Douglas-fir at nutrient-rich and nutrient-poor sites. Decomposition of each litter species declined in a close to linear way throughout 36 months of exposure, with decomposition of beech leaves being slowest. This was likely driven by low initial nitrogen concentration of beech leaves as reflected by strong and long-lasting accumulation of nitrogen which was more pronounced at nutrient-poor sites. Irrespective of litter species, decomposition was slowest in Norway spruce monocultures, with patterns in mixed forests being generally intermediate between those in respective monocultures. Although mechanisms responsible for slow litter decomposition in Norway spruce monocultures remain unclear, the results show that detrimental effects of Norway spruce monocultures can be mitigated by admixture of European beech. The relatively slow decomposition of beech leaves highlights the predominant role of initial litter nutrient concentrations in driving litter decomposition. The slow decomposition of litter in spruce forests highlights that specific environmental conditions in forest stands may strongly modify litter decomposition, with these modifications being similar across litter species. These findings emphasize the importance of understanding how, by shaping the environment, single tree species influence ecosystem functions such as litter decomposition and nutrient cycling. •Litter of European beech decomposes slower than that of Norway spruce and Douglas-fir.•Initial litter nutrient concentrations drive early and late decomposition processes.•Stand type affects litter decomposition irrespective of litter species.•Decomposition in mixed beech - conifer forests is intermediate between monocultures.•Stand type effects on litter decomposition are modulated by stand nutrient status.